Knowledge in Dialogue: Strategies to communicate in archaelogy - Acevedo, Verónica; Muiña, María Florencia; Bertani, Guillermo Oscar (Facultad de Filosofía y Humanidades. Museo de Antropología, 2024)
Foreword. Knowledge in dialogue. Strategies to communicate in archeology.